High glucose induces Drp1-mediated mitochondrial fission via the Orai1 calcium channel to participate in diabetic cardiomyocyte hypertrophy - Wu, Qing-Rui; Zheng, Dan-Lin; Liu, Pei-Ming; Yang, Hui; Li, Lu-An; Kuang, Su-Juan; Lai, Ying-Yu; Rao, Fang; Xue, Yu-Mei; Lin, Ji-Jin; Liu, Shuang-Xin; Chen, Chun-Bo; et al. (Cell death & disease, 2021)
Mitochondrial dysfunction and impaired Ca 2+ handling are involved in the development of diabetic cardiomyopathy (DCM). Dynamic relative protein 1 (Drp1) regulates mitochondrial fission by changing its level of phosphorylation, and the Orai1 (Ca 2+ release-activated calcium channel protein 1) calcium channel is important for the increase in Ca 2+ entry into cardiomyocytes. We aimed to explore the mechanism of Drp1 and Orai1 in cardiomyocyte hypertrophy caused by high glucose (HG). We found that Zucker diabetic fat rats induced by administration of a high-fat diet develop cardiac hypertrophy and impaired cardiac function, accompanied by the activation of mitochondrial dynamics and calcium handling pathway-related proteins. Moreover, HG induces cardiomyocyte hypertrophy, accompanied by abnormal mitochondrial morphology and function, and increased Orai1-mediated Ca 2+ influx. Mechanistically, the Drp1 inhibitor mitochondrial division inhibitor 1 (Mdivi-1) prevents cardiomyocyte hypertrophy induced by HG by reducing phosphorylation of Drp1 at serine 616 (S616) and increasing phosphorylation at S637. Inhibition of Orai1 with single guide RNA (sgOrai1) or an inhibitor (BTP2) not only suppressed Drp1 activity and calmodulin-binding catalytic subunit A (CnA) and phosphorylated-extracellular signal-regulated kinase (p-ERK1/2) expression but also alleviated mitochondrial dysfunction and cardiomyocyte hypertrophy caused by HG. In addition, the CnA inhibitor cyclosporin A and p-ERK1/2 inhibitor U0126 improved HG-induced cardiomyocyte hypertrophy by promoting and inhibiting phosphorylation of Drp1 at S637 and S616, respectively. In summary, we identified Drp1 as a downstream target of Orai1-mediated Ca 2+ entry, via activation by p-ERK1/2-mediated phosphorylation at S616 or CnA-mediated dephosphorylation at S637 in DCM. Thus, the Orai1–Drp1 axis is a novel target for treating DCM.